Further epidemiological investigation of tuberculosis in European bison (Bison bonasus) in Borecka Forest (European Bison Conservation Newsletter, 2018)
European bison (Bison bonasus) is very prone to infection with mycobacteria tuberculosis, which is proven by outbreaks of TB observed in this species since 1996. The International Union for Conservation of Nature (IUCN) has classified the wisent as a threatened species, which is why the monitoring of infectious diseases has to be carried out especially carefully. Because two TB cases have been reported in the European bison of Borecka Forest, the population should be continuously controlled in this respect. Actions have been taken to preliminarily specify the epidemiological situation of tuberculosis in the Borecka Forest wisent population. In total 22 individuals were examined using a commercial interferon-gamma release assay (IGRA) that relies on delayed-type hypersensitivity. Blood collected to lithium heparin tubes was stimulated with bovine and avian tuberculin, as well as with PBS (control). The results were interpreted based on the optical density measured for individual samples, as it is proportional to the amount of interferon-gamma released by T lymphocytes (INF-g - a protein characteristic of the immune response in tuberculosis). To verify negative results of the IGRA, material (mandibular and retropharyngeal lymph nodes) was collected post mortem from 10 of the 22 examined European bison to be tested microbiologically on specific Stonebrink and, additionally, Löwenstein-Jensen media. Although the results of the IGRA were negative, further monitoring of tuberculosis in the Borecka Forest wisent population is considered as necessary in the future.
Keywords: interferon-gamma release assay; European bison; Bison bonasus; tuberculosis